Primary CNS Nonamyloidogenic Light Chain Deposition Disease: Case Report and Brief Review. (December 2017) - Mercado, Juan Jose; Markert, James M.; Meador, William; Chapman, Philip; Perry, Arie; Hackney, James R.
The true incidence of light chain deposition disease (LCDD) restricted to the central nervous system (CNS) is unknown. To our knowledge only 7 cases of LCDD restricted to the brain have been previously reported. We herein describe an unusual example. A 44-year-old man presented with a history of ischemic retinopathy in 2004 and left lower extremity hypoesthesia in 2007 that progressed gradually to left-sided weakness and numbness in the 2 years prior to his hospitalization in 2015. A stereotactic brain biopsy was performed, displaying nonspecific hyaline deposits of amorphous "amyloid-like" material involving deep brain white matter and vessels. These were Congo red negative and were accompanied by a sparse lymphoplasmacytic infiltrate. Plasma cells demonstrated kappa light chain class restriction by chromogenic in situ hybridization (CISH). There was patchy reactivity with kappa immunohistochemistry in the amorphous deposits. A diagnosis of light chain deposition disease was made. Subsequent systemic myeloma and lymphoma workups were negative. Previously reported cases have included men and women, spanning the ages of 19 and 72 years, often presenting with hemiparesis, hypoesthesia, or seizures. Deposits have been reported in the cerebrum and cerebellum. T2/FLAIR (fluid attenuation inversion recovery) changes are usual, but lesions may or may not produce contrast enhancement. The light chain deposition may be of kappa or lambda class. Most lesions have been accompanied by local lymphoid and/or plasma cell infiltrates exhibiting light chain restriction of the same class as the deposits. In summary, LCDD limited to the CNS is a rare lesion consisting of deposition of amyloid-like, but Congo red–negative monotypic light chain usually produced by local lymphoplasmacytic infiltrates.